Modern Britain and the New Imperial History - Thompson, James W. (History compass, 2007)
This article reviews recent trends in British studies, particularly the impact of ‘four nations’ perspectives, and the rise of the new imperial history. It offers a close examination of debates about the relationship between ‘nation’ and ‘empire’ in modern British history, and assesses the strengths and weaknesses of existing approaches. The article identifies the need to integrate accounts of empire's impact upon Britain with a broader comparative perspective that embraces mainland Europe, and to combine more cultural concerns with greater attention to political and economic history.